Synthesis And Evaluation Of Poly (Ethylene) Oxide/erbium Oxide As Potential Diagnostic Nanofibres For Magnetic Resonance Imaging - Jamil, Munirah (2023)
Advances in nanotechnology have led to the development of nanoscale materials for diagnostic applications, with a high potential to improve cancer diagnosis value, significantly impacting the future of healthcare. A diagnostic agent for magnetic resonance imaging (MRI) was developed in the current study using the electrospinning method to embed erbium oxide (Er2O3) nanoparticles in a poly (ethylene) oxide (PEO) matrix. Moreover, the characteristics of PEO and PEO/Er2O3 nanofibres were confirmed using FESEM-EDX, AFM, FTIR, UV-Vis, Zetasizer, HRTEM, XRD, and ICP-OES. In vitro cell cytotoxicity and colony formation studies were conducted on MCF-7 cells to investigate the effects of PEO and PEO/Er2O3 nanofibre formulations on cancer progression characteristics. Findings demonstrated that the polymer blend formulations with and without nanofiller affected fibre diameter, thickness, and surface roughness. Findings also revealed that PEO nanofibres exhibited non-cytotoxic characteristics towards MCF-7 cells. The 5 wt% PEO nanofibre (P5) was recommended as the optimal nanofibre formulation suitable as a polymer matrix or carrier for diagnostic purposes. Further cytotoxicity investigation of PEO/Er2O3 nanofibres demonstrated cell proliferation over nanofiller loading for low dose concentration from 0 – 100 μg/ml, whereas a reduction in cell viability was observed for high dose concentration from 100 – 1000 μg/ml. Nevertheless, none of the formulations inhibited 50% of the cell viability.